Performing Deception Learning, Skill and the Art of Conjuring - Rappert, Brian (Open Book Publishers, 2022)
In Performing Deception, Brian Rappert reconstructs the practice of entertainment magic by analysing it through the lens of perception, deception and learning, as he goes about studying conjuring himself. Through this novel meditation on reasoning and skill, Rappert elevates magic from the undertaking of mere trickery to an art that offers the basis for rethinking our possibilities for acting in the modern world. Performing Deception covers a wide range of theories in sociology, philosophy, psychology and elsewhere in order to offer a striking assessment of the way secrecy and deception are woven into social interactions, as well as the illusionary and paradoxical status of expertise.